Hydrogen bond organic framework, preparation method thereof and adsorbent

The hydrogen bonded organic framework HOF material HIAM-103 synthesized by hydrothermal method solves the problems of high energy consumption and release of toxic substances in existing flue gas, and achieves a low-cost, efficient and safe carbon dioxide capture effect.

CN119859282APending Publication Date: 2025-04-22SHENZHEN POLYTECHNIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510110306.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-22

Smart Images

  • Figure CN119859282A_ABST
    Figure CN119859282A_ABST
Patent Text Reader

Abstract

The molecular formula of the hydrogen bond organic framework is C33H24O12, the hydrogen bond organic framework has a crystal structure, and the space group of the crystal is P31c of a triclinic system. The high-stability porous HOF material with a multi-interpenetrating structure is synthesized through a simple hydrothermal synthesis technology, carbon dioxide is selectively captured from a flue gas (CO2 / N2) binary mixture in a physical adsorption mode, and flue gas purification is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic frameworks, in particular to a hydrogen bond organic framework and a preparation method and an adsorbent thereof. Background Art

[0002] The current process of capturing carbon dioxide in flue gas mainly relies on an organic amine solvent system. The principle of this process is that carbon dioxide reacts chemically with an amine solution to form unstable salts, which are then heated to release carbon dioxide. This process can effectively remove carbon dioxide, but there are obvious deficiencies in the absorption of carbon dioxide by organic amines. The main reason is that the regeneration energy consumption is very high, and the regeneration process may cause the decomposition of amines, resulting in the release of toxic substances. Therefore, it is very necessary to develop a more energy-saving, efficient and safe method for capturing carbon dioxide from flue gas.

[0003] Compared with the carbon dioxide absorption technology of organic amine solution system, the carbon dioxide adsorption separation technology by physical adsorption has significant advantages, including low regeneration energy consumption, high selectivity, and small equipment investment. The core problem of this technology lies in the development of low-cost and high-efficiency porous adsorbents. Hydrogen-bonded organic frameworks (HOFs) are a type of crystalline porous materials formed by self-assembly through complementary hydrogen bonds between molecules. At present, HOF materials are developing rapidly. In addition to the framework structure characteristics and high specific surface properties similar to MOF and COF, HOF itself has flexible and reversible hydrogen bonding, which gives it unique properties such as easy purification, high crystallinity, solution processability and self-healing. It has great application potential in the field of gas adsorption and separation. Although some HOFs have been reported to be used to selectively adsorb carbon dioxide from flue gas, these HOF materials are unstable in structure because they are only connected by a single hydrogen bond, and most of them use organic solutions for long-term diffusion synthesis, which has high time cost, and the treatment of waste liquid is easy to cause secondary pollution to the environment. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a hydrogen-bonded organic framework (HOF) material with high stability and green and pollution-free, which is used for capturing carbon dioxide in flue gas.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A hydrogen-bonded organic framework with the molecular formula C 33 H 24 O 12 , named HIAM-103, has a crystal structure, and the space group of the crystal is P of the triclinic system. 31c .

[0006] Preferably, the HIAM-103 is a porous material synthesized by a hydrothermal method using 1,3,5-trimethyl-2,4,6-tri(3',5'-dicarboxyphenyl)benzene H6TMBTI as a raw material.

[0007] Furthermore, in the crystal structure, each H6TMBTI building block is connected to six adjacent building blocks through hydrogen bonds; the bond angle and bond length of OH…O in the hydrogen bonds are 167.8 / 175.9° and The interconnected H6TMBTI units form an ACS topological network; four identical networks interpenetrate each other to form a methyl-rich one-dimensional channel.

[0008] Furthermore, the three-dimensional crystal structure of HIAM-103 has a triangular one-dimensional pore structure with a specific surface area of ​​578.8 cm 2 / g, pore size distribution is concentrated in

[0009] The crystallographic parameters of HIAM-103 are as follows:

[0010] The present invention provides a preparation method for preparing the hydrogen-bonded organic framework described in the above embodiment, comprising the following steps: Step S1, preparing a reaction system: ultrasonically dispersing 1,3,5-trimethyl-2,4,6-tris(3',5'-dicarboxyphenyl)benzene in a solvent to obtain a reaction system mixture; Step S2, performing a hydrothermal synthesis reaction: the reaction system mixture reacts at a predetermined reaction temperature for a predetermined time to obtain a mixture containing HAIM-103; Step S3, filtering and washing to obtain HAIM-103 crystal powder.

[0011] In some embodiments, the solvent is water or formic acid; and the reaction temperature is 120-180°C.

[0012] Furthermore, the preparation method further comprises: Step S4, activating the HAIM-103 crystals to obtain an adsorbent material; The step S is to activate the crystals in a dynamic vacuum at an activation temperature of 60 to 100° C. to obtain activated HAIM-103 crystal materials, which are used as adsorbents.

[0013] The present invention provides an adsorbent, which is the hydrogen-bonded organic framework described in the above embodiment, and uses a physical adsorption method to selectively capture carbon dioxide from flue gas to achieve flue gas purification.

[0014] In some embodiments, the adsorption temperature of the physical adsorption method is 0-50°C, and the adsorption pressure is 0-2 bar; the desorption temperature is 60-120°C, and the desorption pressure is 0.005-1.0 bar; the physical adsorption method uses a fixed bed.

[0015] The beneficial effects of the present invention are: The present invention synthesizes a highly stable porous HOF material with a multi-interpenetrating structure through a simple hydrothermal synthesis technology, and selectively captures carbon dioxide from a binary mixture of flue gas (CO2 / N2) by physical adsorption to achieve flue gas purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The figure is a coordination diagram of different building blocks of the hydrogen-bonded organic framework HOF material HAIM-103 of the present invention, wherein (a) shows the coordination environment of HAIM-103, and (b) shows a schematic structural diagram of HAIM-103.

[0017] Figure 2 The X-ray diffraction pattern of the material of HAIM-103 obtained in Example 1 of the present invention is shown in FIG. Figure 2 It can be seen that the powder X-ray diffraction of the synthesized sample is consistent with the simulated Figure 1 The results show that the synthesized HAIM-103 sample has high purity and has no obvious effect on the structure of HAIM-103 material after activation and testing.

[0018] Figure 3 This is the N2 adsorption-desorption isotherm of the HAIM-103 material obtained in Example 1 of the present invention at 77K. Figure 3 It can be seen that the HAIM-103 material is a microporous material.

[0019] Figure 4 The adsorption isotherms of carbon dioxide and nitrogen at room temperature for the HAIM-103 material synthesized in Example 1 of the present invention as an adsorbent are shown in FIG. Figure 4 It can be seen that the HAIM-103 material exhibits a much higher adsorption capacity for carbon dioxide than for nitrogen, proving the preferential adsorption of carbon dioxide by the HAIM-103 material.

[0020] Figure 5 The selectivity of the HAIM-103 material synthesized in Example 1 of the present invention to carbon dioxide and nitrogen is shown in FIG. Figure 5 It can be seen that the selectivity of carbon dioxide to nitrogen at 1 bar is close to 50, which proves that HIAM-103 has excellent selectivity for carbon dioxide / nitrogen.

[0021] Figure 6The dynamic breakthrough curve of the HAIM-103 material synthesized in Example 1 and Example 2 of the present invention as an adsorbent is shown in FIG. Figure 6 It can be seen that under dry and 50% RH conditions, nitrogen passes through the adsorption column before carbon dioxide, and carbon dioxide is detected after a period of time, which proves that the HAIM-103 material can selectively adsorb carbon dioxide under dry and humid conditions to achieve flue gas purification.

[0022] Figure 7 The cyclic dynamic breakthrough curve of the HAIM-103 material obtained in Example 2 as an adsorbent. Figure 7 It can be seen that at 50% RH, the synthesized HAIM-103 material maintains good carbon dioxide capture performance during multiple cycles, proving the cyclic stability of the HAIM-103 material and its ability to capture carbon dioxide under long-term humidity conditions. DETAILED DESCRIPTION

[0023] The exemplary embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.

[0024] It should be understood that the terms used herein are only for the purpose of describing specific example embodiments and are not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms "one", "an" and "said" as used herein may also be meant to include plural forms. The terms "include", "comprise", "contain", and "have" are inclusive, and therefore specify the existence of stated features, steps, operations, elements and / or parts, but do not exclude the existence or addition of one or more other features, steps, operations, elements, parts, and / or combinations thereof. The method steps, processes, and operations described herein are not interpreted as necessarily requiring them to be performed in the specific order described or illustrated, unless the execution order is clearly indicated. It should also be understood that additional or alternative steps may be used.

[0025] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0026] The endpoints and any values ​​of the endpoint values ​​disclosed in the present invention are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0027] The present invention uses low-cost 1,3,5-trimethyl-2,4,6-tris(3',5'-dicarboxyphenyl)]benzene (H6TMBTI) as raw material and synthesizes a highly stable hydrogen-bonded porous material HOF by a simple rapid hydrothermal method. The molecular formula is: C 33 H 24 O 12 , named HIAM-103 (HIAM: Hoffman institution of advanced material). The reaction principle is that the H6TMBTI organic ligand is ultrasonically dispersed in the solution, and then in the subsequent high-temperature process, the molecular self-assembly forms a rod-shaped hydrogen-bonded organic framework material (HIAM-103) with one-dimensional channels. The crystal structure of HIAM-103 was determined by X-ray single crystal diffraction analysis, and the space group of the crystal is the P of the triclinic system. 31c In the crystal structure, each H6TMBTI building block is connected to six adjacent building blocks through 12 hydrogen bonds. The bond angle and bond length of OH…O in the hydrogen bond are 167.8 / 175.9° and The interconnected H6TMBTI units form an acs topological network. Four identical networks interweave to form a methyl-rich one-dimensional channel with a diameter of approximately

[0028] The hydrogen bond organic framework HOF material HAIM-103 of the present invention has the following coordination of different building blocks: Figure 1 As shown, the coordination environment is shown in (a) and the structural schematic diagram is shown in (b). The crystal structure of HIAM-103 was obtained through X-ray single crystal diffraction analysis. (a) shows the specific coordination mode between different atoms. Each H6TMBTI building unit is connected to the adjacent building units through hydrogen bonds. (b) shows the three-dimensional crystal structure of HIAM-103. It can be seen that there are obvious triangular one-dimensional channels in the structure. The pore structure has been tested by nitrogen adsorption at 77K, indicating that its specific surface area is 578.8cm 2 / g, the pore size distribution is mainly concentrated in

[0029] Table 1 below shows the crystallographic parameters of the hydrogen bond organic framework HOF material of the present invention: Table 1 Crystallographic parameters

[0030] The hydrogen bond porous material HOF (HIAM-103) compound of the present invention provides a suitable pore size and pore chemical environment for the adsorption of carbon dioxide molecules, can generate a strong force with carbon dioxide, and the abundant -CH3 functional groups in the pores can resist the erosion of the structure by water molecules, thereby achieving the ability to completely capture carbon dioxide from the binary mixture of flue gas and purify the flue gas in one step. The present invention synthesizes a highly stable porous HOF material with a multiple interpenetrating structure through a simple hydrothermal synthesis technology, which is suitable for selectively capturing carbon dioxide from the binary mixture of flue gas (CO2 / N2) by physical adsorption to achieve flue gas purification.

[0031] In the first aspect, the present invention provides a hydrogen bond porous material HOF (HIAM-103), the molecular formula of which is: 33 H 24 O 12 The compound is a hydrogen-bonded organic framework material generated by the reaction of 1,3,5-trimethyl-2,4,6-tri(3',5'-dicarboxyphenyl)benzene (H6TMBTI) under a hydrothermal environment.

[0032] In the second aspect, the method for preparing the hydrogen bond porous material HOF (HIAM-103) of the present invention, the specific reaction steps are as follows: Step S1, preparing a reaction system: ultrasonically dispersing 1,3,5-trimethyl-2,4,6-tris(3',5'-dicarboxyphenyl)benzene in a certain amount of solvent, and then transferring the reaction system mixture into a reaction kettle (e.g., a stainless steel reaction kettle lined with Teflon); Step S2, performing a hydrothermal synthesis reaction: placing the reactor in an oven and reacting at a predetermined reaction temperature for a predetermined time to obtain a mixture containing HOF; Step S3, filtering and washing: filtering the mixture containing HOF to obtain HOF yellow powder, and washing with water three times (not limited to three times) to obtain HOF crystal powder; Step S4, activating the HOF crystals to obtain an adsorbent material: activating the crystals in a dynamic vacuum at a predetermined activation temperature for 2 hours (not limited to 2 hours) to obtain an activated HOF crystal material that can be used as an adsorbent.

[0033] Among them, the above-mentioned raw material reactant is only 1,3,5-trimethyl-2,4,6-tris(3',5'-dicarboxyphenyl)benzene.

[0034] Ultrasonic dispersion can be carried out at room temperature for about ten minutes. Conventional ultrasound can be used to evenly disperse the raw material reactants in the solvent.

[0035] Preferably, the solvent is water or formic acid; more preferably, the solvent is water.

[0036] Preferably, the ratio of the reactant 1,3,5-trimethyl-2,4,6-tris(3',5'-dicarboxyphenyl)benzene to the solvent is 3 to 8 mL of solvent per 1 mmol of 1,3,5-trimethyl-2,4,6-tris(3',5'-dicarboxyphenyl)benzene; more preferably, 5 mL of solvent is added per 1 mmol of H6TMBTI.

[0037] Preferably, the reaction temperature is 120-180°C; more preferably, the reaction temperature is 150°C.

[0038] Preferably, the activation temperature of the above-mentioned crystalline powder is 60-100°C, and preferably, the activation temperature is 80°C.

[0039] In a third aspect, the present invention also provides a method of using the above HOF as an adsorbent to selectively adsorb carbon dioxide in flue gas, thereby achieving one-step purification of flue gas.

[0040] As an embodiment, flue gas (for example, a binary mixed gas of simulated carbon dioxide and nitrogen) is passed through the synthesized HIAM-103 adsorbent, and the adsorbent selectively adsorbs carbon dioxide in the mixed gas, thereby achieving carbon dioxide capture in the flue gas.

[0041] The gas can be subjected to one or more combinations of adsorption methods such as pressure swing adsorption with a fixed bed, temperature swing adsorption or low-pressure adsorption desorption. At the set adsorption temperature and pressure, the mixed gas enters the fixed bed filled with HIAM-103 adsorbent at a set flow rate. Nitrogen penetrates the bed first, and carbon dioxide is enriched in the adsorption bed. After carbon dioxide penetrates, the bed is regenerated by desorption and the next cycle is carried out.

[0042] Preferably, the adsorption temperature is 0-50° C., and the adsorption pressure is 0-2 bar; the desorption temperature is 60-120° C., and the desorption pressure is 0.005-1.0 bar.

[0043] Embodiment 1: In this example, 1,3,5-trimethyl-2,4,6-tri(3',5'-dicarboxyphenyl)]benzene (0.1 mmol) was ultrasonically dispersed in H2O (5 mL), and then the mixture was transferred to a Teflon-lined reactor and placed in a 150°C oven for reaction for 2 days. The product HIAM-103 was obtained by filtration; then it was washed with water five times, and the obtained HIAM-103 crystal powder was vacuum dried at 60°C for 2 hours to obtain an activated adsorbent.

[0044] Figure 2The X-ray diffraction pattern of the HIAM-103 material obtained in Example 1 is shown. Figure 2 Available, synthesized HIAM-103 powder X-ray diffraction and simulation Figure 1 The results show that the synthesized HIAM-103 has high purity and has no obvious effect on the material structure after activation and testing.

[0045] Figure 3 The figure shows the N2 adsorption-desorption isotherm of the HIAM-103 material obtained in Example 1 at 77K. Figure 3 It can be seen that the HIAM-103 material is a microporous material.

[0046] Figure 4 The adsorption isotherms of carbon dioxide and nitrogen of the HIAM-103 material synthesized in Example 1 at room temperature are shown. Figure 4 It can be seen that the HIAM-103 material shows that the adsorption amount of carbon dioxide is much higher than that of nitrogen, which proves the preferential adsorption of carbon dioxide by the material.

[0047] Figure 5 The figure shows the selectivity of the HIAM-103 material synthesized in Example 1 to carbon dioxide and nitrogen. Figure 5 It can be seen that the selectivity of carbon dioxide to nitrogen at 1 bar is close to 50, which proves that the HIAM-103 material has excellent selectivity for carbon dioxide / nitrogen.

[0048] Figure 6 The following are the dynamic penetration curves of the HIAM-103 material obtained in Example 1 and Example 2. Figure 6 It can be seen that under dry and 50% RH conditions, nitrogen passes through the adsorption column before carbon dioxide, and carbon dioxide is detected after a period of time, which proves that the HIAM-103 material can selectively adsorb carbon dioxide under dry and humid conditions to achieve flue gas purification.

[0049] Embodiment 2: In this example, 1,3,5-trimethyl-2,4,6-tri(3',5'-dicarboxyphenyl)]benzene (0.1 mmol) was ultrasonically dispersed in formic acid (5 mL), and then the mixture was transferred to a Teflon-lined reactor and placed in a 150°C oven for reaction for 2 days. The product HIAM-103 was obtained by filtration; then it was washed with formic acid five times, and the obtained HIAM-103 crystal powder was vacuum dried at 60°C for 2 hours to obtain an activated adsorbent.

[0050] Figure 7The figure shows the cyclic dynamic penetration curve of the HIAM-103 material obtained in Example 2 as an adsorbent. As can be seen from the figure, at 50% RH, the synthesized HIAM-103 material maintains good carbon dioxide capture performance during multiple cycles, proving the cyclic stability of the HIAM-103 material and the better capture capacity of carbon dioxide under long-term humidity conditions.

[0051] Embodiment three: In this embodiment, 1,3,5-trimethyl-2,4,6-tri(3',5'-dicarboxyphenyl)benzene (1 mmol) was ultrasonically dispersed in formic acid (10 mL), and then the mixture was transferred to a Teflon-lined reactor and placed in an oven at 180°C for reaction for 2 days; the product HIAM-103 was obtained by filtration; then the product was washed with formic acid five times, and the obtained HIAM-103 crystalline powder was vacuum dried at 60°C for 2 hours to obtain an activated adsorbent.

[0052] Application Example 1

[0053] In this example, the HIAM-103 material obtained in Example 3 was loaded as an adsorbent into a fixed bed (inner diameter 5 mm, volume 2 ml) adsorption column, and the two-component gas of carbon dioxide / nitrogen (molar ratio of 15 / 85) was flowed through the adsorption column at a flow rate of 4.0 mL / min at 25° C. and a back pressure of 1 bar. High-purity nitrogen (>99%) was detected at the tail end of the adsorption column. When carbon dioxide completely penetrated, the adsorption was stopped, and the adsorption column was purged with helium at 120° C. to achieve cyclic regeneration. Alternatively, at room temperature, a vacuum pump was used for desorption and regeneration, and the vacuum degree was 0.05 bar.

[0054] Application Example 2

[0055] In this embodiment, the HIAM-103 material obtained in Example 3 is loaded as an adsorbent into a fixed bed (inner diameter 5 mm, volume 2 ml) adsorption column, and at 25°C and 1 bar back pressure, the two-component gas of carbon dioxide / nitrogen (molar ratio of 15 / 85) is passed through a steam generator at a flow rate of 4.0 mL / min, so that the humidity of the gas is 50% RH, and then the gas flows through the adsorption column, and high-purity nitrogen (>99%) is detected at the tail end of the adsorption column. When carbon dioxide completely penetrates, adsorption is stopped, and at 120°C, helium is purged to achieve cyclic regeneration of the adsorption column. Alternatively, at room temperature, desorption and regeneration are performed using a vacuum pump, and the vacuum degree is 0.05 bar.

[0056] The present invention synthesizes a new compound HIAM-103, and utilizes the compound to preferentially adsorb carbon dioxide from a binary mixture of flue gas to achieve the ability of flue gas purification. It is expected to replace the high-energy consumption organic amine-solution carbon dioxide absorption process currently used in industry, and has great application potential in the field of carbon capture in industrial flue gas.

[0057] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A hydrogen-bonded organic framework having the molecular formula C 33 H 24 O 12 , named HIAM-103, has a crystal structure, and the space group of the crystal is P of the triclinic system. 31c .

2. The hydrogen-bonded organic framework according to claim 1, characterized in that: The HIAM-103 is a porous material synthesized by a hydrothermal method using 1,3,5-trimethyl-2,4,6-tri(3',5'-dicarboxyphenyl)]benzene H6TMBTI as a raw material.

3. The hydrogen-bonded organic framework according to claim 2, characterized in that: In the crystal structure, each H6TMBTI building unit is connected to six adjacent building units through hydrogen bonds; the bond angle and bond length of OH‧‧‧O in the hydrogen bonds are 167.8 / 175.9° and 1.567 / 1.868Å, respectively. The interconnected H6TMBTI units form an acs topological network; four identical networks are intertwined to form a methyl-rich one-dimensional channel.

4. The hydrogen-bonded organic framework according to claim 3, characterized in that: The three-dimensional crystal structure of HIAM-103 has a triangular one-dimensional pore, and the specific surface area of ​​the pore structure is 578.8 cm 2 / g, pore size distribution is concentrated at 6 Å; The crystallographic parameters of HIAM-103 are as follows: 。 5. The hydrogen-bonded organic framework according to claim 1, characterized in that: The coordination environment of the crystal structure of HAIM-103 is: ; The crystal structure of HAIM-103 is: 。 6. A preparation method for preparing the hydrogen-bonded organic framework according to any one of claims 1 to 5, comprising the following steps: Step S1, preparing a reaction system: ultrasonically dispersing 1,3,5-trimethyl-2,4,6-tris(3',5'-dicarboxyphenyl)benzene in a solvent to obtain a reaction system mixture; Step S2, performing a hydrothermal synthesis reaction: the reaction system mixture reacts at a predetermined reaction temperature for a predetermined time to obtain a mixture containing HAIM-103; Step S3, filtering and washing to obtain HAIM-103 crystal powder.

7. The preparation method according to claim 6, characterized in that: The solvent is water or formic acid; the reaction temperature is 120-180°C.

8. The preparation method according to claim 6, characterized in that: The preparation method further comprises: Step S4, activating the HAIM-103 crystals to obtain an adsorbent material; The step S is to activate the crystals in a dynamic vacuum at an activation temperature of 60-100° C. to obtain activated HAIM-103 crystal materials, which are used as adsorbents.

9. An adsorbent, which is the hydrogen-bonded organic framework according to any one of claims 1 to 5, and which selectively captures carbon dioxide from flue gas by a physical adsorption method to achieve flue gas purification.

10. The adsorbent according to claim 9, characterized in that: The adsorption temperature of the physical adsorption method is 0-50°C, and the adsorption pressure is 0-2 bar; the desorption temperature is 60-120°C, and the desorption pressure is 0.005-1.0 bar; the physical adsorption method adopts a fixed bed.